Propagation characteristics of longitudinal-torsion coupled waves in phononic crystal rods of chiral materials (Archives of Mechanics - Test, 2023)
The chiral properties of chiral materials have a great influence on the wave propagation. Applying chiral materials to the design of phononic crystal rods not only increases the design space, but also may have other potential advantages. There is a lack of research on designing phononic crystal rods using chiral materials and the propagation characteristics of elastic waves in phononic crystal rods made of chiral materials. In this study, chiral materials are introduced into the design of phonon crystal rods for the first time, Bragg scattering type and local resonance type phononic crystal rods are designed using chiral materials Dispersion equations for the propagation of longitudinal-torsion coupled waves in the phononic crystal rods are derived, and the effect of the chirality of the materials on their bandgap range is studied. The study shows that: in Bragg scattering type phonon crystal rods, material chirality can greatly affect the bandgap, among them, the chiral direction has the greatest effect, and in order to obtain a low-frequency wide bandgap, the chiral coefficients of the materials should be increased as much as possible with the chiral directions of the two cells being opposite; in the local resonance type phonon crystal rod, only two types of oscillators are added to the material simultaneously to produce a band gap, and the starting frequency obtained is much lower than that of the Bragg scattering type.